Evaluation of the Early Impact of COVID-19 on Physiotherapy Clinical Placement Learning Models and Client Case-Mix - Hams, Andrea; Jones, Taryn (International Journal of Practice-based Learning in Health and Social Care, 2022)
<span class="NormalTextRun SCXW107163016 BCX9" data-ccp-parastyle="Abstract" data-ccp-parastyle-defn=""ObjectId":"b47c2e9b-1c45-4431-a494-7d75e1b9e163|221","ClassId":1073872969,"Properties":[469775450,"Abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"Abstract",335572020,"1",469777841,"Times New Roman",469777842,"Arial",469777843,"Times New Roman",469777844,"Times New Roman",469769226,"Times New Roman,Arial",268442635,"20",335559685,"709",335559737,"425",335559740,"240",201341983,"0",335559739,"200",335551550,"6",335551620,"6",469777929,"Abstract Char",469775498,"Keywords",469778324,"Normal",469778325,"["Comments"]"]" data-ccp-parastyle-linked-defn=""ObjectId":"97460671-e287-4768-a5fa-32d0c30b3204|3","ClassId":1073872969,"Properties":[469775450,"Abstract Char",201340122,"1",134233614,"true",469778129,"AbstractChar",335572020,"1",134231262,"true",469777841,"Times New Roman",469777842,"Arial",469777843,"Times New Roman",469777844,"Times New Roman",469769226,"Times New Roman,Arial",469777929,"Abstract",469778324,"Default Paragraph Font",469778325,"["Comments Char"]"]">Clinical placements are fundamental to entry-level physiotherapy education and provide an opportunity for students to translate theory into practice within authentic clinical environments. Student success during clinical placement is a core requirement of physiotherapy programs and a critical component of the pathway to graduation, registration, and then employment. The registration of a physiotherapist confirms that as a student, they have met the profession’s rigorous accreditation requirements. COVID-19 has significantly disrupted physiotherapy clinical placements across Australia, with many placements postponed or cancelled in the early public health response. These placement disruptions may preclude students from demonstrating mandatory pre-registration accreditation requirements, ultimately reducing the number of eligible new-graduate physiotherapists. Creating sustainable clinical placements whilst upholding the professional standard of entry level graduates during the pandemic, calls for innovative solutions to monitor student placement experiences. A Clinical Portfolio was implemented to improve monitoring processes and enable dynamic responses to potentially altered student learning experiences as COVID-19 public health measures evolved. In doing so, the aim of this study was to evaluate the impact of COVID-19 on physiotherapy student placements between May and June 2020 through examining client case-mix, demographics and learning model documented in each student’s Clinical Portfolio. These data sets allowed for comparison of learning model and case-mix during the pandemic with previous literature monitoring typical physiotherapy clinical placement experience, and providing support for ensuring the registration of the cohort impacted.